Explorations within India for collection of cotton species germplasm - Singh, V.V.=700 1 Mohan, P.; Kulkarni, V.N.; Baitule, S.J.; Pathak, B.R.
(En, Fr, Es)
ilus., 6 ref.
Keywords: GERMOPLASMA; COLECCIONES; BANCO DE GENES; GOáYPIUM; ITALIA